Perempuan Pencari Nafkah Selama Pandemi Covid-19 - Eka Kartika Sari; Biko Nabih Fikri Zufar (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The perception of women as the number two role in society continues to this day. This knowledge has an impact on women's inferiority and subordination. In addition, the conditions of the Covid-19 pandemic have increased the workload for women at home. The workload for women has increased threefold, including earning a living in it. The woman breadwinner in Kampung Kue Rungkut Lor II experienced this during the pandemic. This article uses qualitative research methods and a phenomenological approach, in order to obtain data on the quality of life in the Kampung Kue Rungkut Lor II community. The purpose of this study was to determine descriptively the condition of women breadwinners during the pandemic. As a result, the “Pembatasan Sosial Berskala Besar” (PSBB) affected the economic conditions in the Kampung Kue Rungkut Lor II community, and women also experienced three times more workload than men at home. The pandemic has actually added to the exploitation and oppression of women in the Kampung Kue Rungkut Lor II community. Therefore, it is necessary to have further research on the quality of life of women breadwinners in Kampung Kue Rungkut Lor II before the pandemic to find out the differences in the quality of life of women breadwinners in the same location.